Antioxidant activities of sea buckthorn polysaccharides and their potential application in cosmetic industry - Hao Wang; Na Cheng; Qingyuan Wu; Danjiao Fang; Faiz-Ur Rahman; Huifang Hao; Yongmin Zhang (Journal of Dermatologic Science and Cosmetic Technology, 2024)
Background: Many natural polysaccharides have been reported to protect against skin aging through antioxidant pathways, but sea buckthorn polysaccharides have been less well studied in terms of antioxidant activity, and the related studies are not well developed. Objective: By examining the chemical structure of sea buckthorn polysaccharides, this research aimed to offer a scientific foundation for their use in cosmetics and explore the in vitro antioxidant potential of these polysaccharides. Materials: and Methods: We made SP (sea buckthorn crude polysaccharide) using both hot water extraction and ultrasonic extraction. Then, we used the anion exchange method to separate and purify it to get three different polysaccharides: SPA (polysaccharide eluted from deionized water), which is a neutral polysaccharide, and SPB (polysaccharides eluted from 0.1 M NaCl) and SPC (polysaccharide eluted from 0.2 M NaCl), which are acidic polysaccharides. The characteristics of the four polysaccharides (SP, SPA, SPB and SPC) were determined using high-performance gel permeation chromatography (HPGPC), high-performance liquid chromatography (HPLC), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and x-ray diffractometry (XRD). In vitro antioxidant assays were used to test their antioxidant activities. Results: The in vitro antioxidant assay showed that the four sea buckthorn polysaccharides (SP, SPA, SPB, and SPC) were good at getting rid of superoxide anion and DPPH radicals, especially ABTS radicals. They were also better at getting rid of free radicals than VC at low concentrations, and they were also good at reducing other molecules. Conclusion: These results showed that sea buckthorn polysaccharide has certain antioxidant activity; therefore, sea buckthorn polysaccharide has a strong potential to be applied in antioxidant and anti-aging functional cosmetics.